2005
DOI: 10.1128/jb.187.3.1135-1160.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Analysis Indicates that FNR ofEscherichia coliK-12 Regulates a Large Number of Genes of Unknown Function

Abstract: The major regulator controlling the physiological switch between aerobic and anaerobic growth conditions in Escherichia coli is the DNA binding protein FNR. To identify genes controlled by FNR, we used Affymetrix Antisense GeneChips to compare global gene expression profiles from isogenic MG1655 wild-type and ⌬fnr strains grown in glucose minimal media under aerobic or anaerobic conditions. We found that 297 genes contained within 184 operons were regulated by FNR and/or by O 2 levels. The expression of many g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
221
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(245 citation statements)
references
References 95 publications
16
221
2
Order By: Relevance
“…Though other transcription factors may also be responsible, the expression of RavA-ViaA during oxygen starvation was found to be primarily inducible by the transcriptional regulator Fnr, which also regulates the expression of the Frd complex as well as other proteins involved in anaerobiosis [29,41].Our finding of the regulation of the ravAviaA promoter by Fnr is consistent with a recent high throughput study based on a…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…Though other transcription factors may also be responsible, the expression of RavA-ViaA during oxygen starvation was found to be primarily inducible by the transcriptional regulator Fnr, which also regulates the expression of the Frd complex as well as other proteins involved in anaerobiosis [29,41].Our finding of the regulation of the ravAviaA promoter by Fnr is consistent with a recent high throughput study based on a…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
“…ACCEPTED MANUSCRIPT 9 expression of a large number of genes during the transition from aerobiosis to anaerobiosis [28,29]. The co-expression of genes under Fnr control suggested that Fnr was also likely to regulate the expression of both ravA and viaA.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In C. glutamicum, and again similar to what is observed in B. subtilis (Ye et al, 2000) and E. coli (Kang et al, 2005), numerous other genes are induced or repressed with changes in environmental conditions such as oxygen tension. Among the genes observed to be highly inducible in the last two species, beyond those genes involved in anaerobic respiration, carbon metabolism and electron transport, iron uptake, stress response and several hypothetical genes are also upregulated.…”
Section: Discussionmentioning
confidence: 57%
“…Among the genes observed to be highly inducible in the last two species, beyond those genes involved in anaerobic respiration, carbon metabolism and electron transport, iron uptake, stress response and several hypothetical genes are also upregulated. In B. subtilis and E. coli, the major regulator of the physiological switch between aerobic and anaerobic growth conditions is the DNA binding protein FNR (Gunsalus & Park, 1994;Kang et al, 2005;Pao et al, 1994;Ye et al, 2000). For example, in E. coli, 297 genes constituting 184 different operons are regulated by FNR and/or oxygen levels (Kang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic structure of Crp/Fnr is a C-terminal helix-turn-helix (HTH) motif that fits the DNA major groove and an N-terminal nucleotide binding domain (34). This class of transcriptional factors is named after the first two representatives discovered in Escherichia coli, i.e., the Crp (cyclic AMP [cAMP] receptor protein) and Fnr (fumarate and nitrate reductase regulator protein) (4,21,24,27). Crp/Fnr regulators are generally classified into different subfamilies (e.g., CooA, Crp, Dnr, FixK, Fnr, HbaR, NnrR, etc.)…”
mentioning
confidence: 99%